Management of pediatric burn injuries in a tertiary center in North-East Slovenia: Obravnava otroških opeklin v terciarnem centru v SV Sloveniji - Dukić Vuković, Tanja; Gregorič, Minja (Acta Medico-Biotechnica, 2023)
Purpose: Burns are serious injuries that cause permanent functional, aesthetic, and psychosocial consequences. This study aimed to examine the incidence of pediatric burns requiring hospitalization, and different treatment modalities and outcomes.Methods: In this retrospective observational study, 28 children with burns (19 boys and nine girls) were admitted between 2014 and 2018 for treatment. We monitored the incidence of burns and analyzed different treatment modalities and treatment outcomes. Children in this study were treated at the Pediatric Intensive Care Unit and the Department of Plastic and Reconstructive Surgery of the University Medical Centre Maribor.Results: Scalds were found to be the most common type of burns in children (68%). Children younger than 5 years of age were the most affected (75%). The average burned total body surface area was 9%. Furthermore, 89% of children needed surgical treatment. The hospitalization lasted for an average of 14.6 days, with complete healing occurring in 72% of children within 4 weeks. Conclusions: This study showed that the most vulnerable age group of children with severe burns who required hospitalization was between 1 and 2 years and that the most common type of burn was scalding. We suggested educating parents about burns and burn injuries and how such serious incidence could be prevented, especially among the youngest children.